Synthesizing postpartum care pathways, facilitators, and barriers for women after cesarean section: a qualitative analysis from rural Rwanda - Brittany L Powell; Theoneste Nkurunziza; Fredrick Kateera; Leila Dusabe; Marthe Kubwimana; Rachel Koch; Bethany L Hedt-Gauthier; Robert Riviello (Journal of Global Health Reports)
# Background In low- and middle-income countries (LMICs), c-section is the most commonly performed operation, and surgical site infection (SSI) is the most common post-operative complication following all surgical procedures performed. Whilst multiple interventions have been rolled out to address high SSI rates, strategies for optimal care of patients at risk of developing SSIs need to include an understanding of the general care seeking behaviors, facilitators, and barriers among high-risk groups, including mothers delivering via c-section. This study explores the healthcare experiences of women who delivered by c-section section, from giving birth through recovery, and their associated decision-making, perceptions of care, and social and financial supports.